Multi-media Utilization in Teaching-Learning Process - Mary Jane O. Gelacio,; Sheena Mae T. Comighud, (IJRDO- Journal of Educational Research, 2020)
This study aimed to determine the utilization of multi-media in teaching learning process in Manalongon Nicolas N. Lajot Central School, Sta. Catalina District I, involving 95 respondents of 46 male and 49 female, using the whole population of Grade V during the SY 2017-2018. This study is a descriptive design as the main data gathering instrument. The modified questionnaire was based on the questionnaire of Demetrio Catid. Since this was a modified questionnaire, the trial run was conducted in Mabuhay Elementary School, to find out the internal reliability and consistency of the items the researcher used cronbach alpha. The questionnaire was divided into two parts. Part one was the respondent’s demographic profile and part two was the areas of multi-media utilization in teaching-learning process. The study utilized the frequency distribution, percentage, weighted mean and composite mean for the statistical treatment. Findings revealed the following: The composite mean obtained in the following areas were: learner’s motivation 3.56 (Very Helpful), learner’s cognition 3.49 (Very Helpful), learner’s interaction 3.44 (Very Helpful), the learner’s engagement 3.22 (Very Helpful). Recommendations included the following: that the teachers must be computer literate; that multimedia be used frequently in teaching to encourage learners to be active in the class, that the school must have enough computer units and a skilled personnel to maintain and secure the technological devices prey from vandals.performance.